PENGEMBANGAN MODUL FISIKA BERBASIS KEARIFAN LOKAL PERMAINAN TRADISIONAL KALIMANTAN TENGAH PADA MATERI MOMENTUM DAN IMPULS - Nur Laily Makhmudah; Subiki Subiki; Supeno Supeno (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract Based on interviews with one of the SMAN 1 Sampit physics teachers, teaching materials used are still less related to the surrounding environment, while the 2013 curriculum requires contextual learning so that learning is more meaningful. Central Kalimantan has a variety of local wisdom, one of which is traditional games. Basic knowledge of traditional Central Kalimantan traditional games, has never been associated with physics learning. Based on this problem, the development of a local wisdom-based module is needed. This development research using Nieveen's development model consists of three stages, namely preliminary research, prototyping stage, and assessment stage, the purpose of this study is to describe student learning outcomes after using local wisdom-based physics modules. Field trials were conducted in class X MIPA B SMAN 1 Sampit with a total of 33 students. Student learning outcomes consisted of pretest and posttest scores, the average pretest score was 23.64 and the posttest was 72.67, with an average difference of 49.03. Learning outcomes analyzed using N-gain got the medium criteria with a result of 0.65%. Physics Module based on traditional game of Central Kalimantan can improve student learning outcomes and is suitable for use in physics learning material momentum and impulses. Key word: Physics module, Local wisdom, Learning outcomes